If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5y + -9 = 7 + y Reorder the terms: -9 + 5y = 7 + y Solving -9 + 5y = 7 + y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1y' to each side of the equation. -9 + 5y + -1y = 7 + y + -1y Combine like terms: 5y + -1y = 4y -9 + 4y = 7 + y + -1y Combine like terms: y + -1y = 0 -9 + 4y = 7 + 0 -9 + 4y = 7 Add '9' to each side of the equation. -9 + 9 + 4y = 7 + 9 Combine like terms: -9 + 9 = 0 0 + 4y = 7 + 9 4y = 7 + 9 Combine like terms: 7 + 9 = 16 4y = 16 Divide each side by '4'. y = 4 Simplifying y = 4
| 60-what+10=20 | | 5=1-4(-5) | | 3m-7=m-13 | | 3x+9x+5=17 | | 4-5p=8 | | 2(X+8)+5x-9=3(X+2)+4(2x+9)-5(3x+8)+25-12x | | 3x^2=89 | | 5v^2-8v-21=0 | | 10y-21=7y | | 4b+7=15 | | 7x+11=x-2510 | | 2x+5=11yforx | | -38=-2n | | 3x+29y=-17 | | x/4-(4x-10)/5=7/10x | | p/3=3(y-5X)/2 | | [5x+3]+10=7 | | 9(3x+10)+20=50 | | 655=v-543 | | 2x+5=11forx | | 3y-2+y+50=5+6y+45-4y | | p/5=3(y-5X)/2 | | X+(x+7)=49 | | 2(z+.5)=8-z | | 7x-4x-3=118 | | 5+12x-2=8x+27-2x | | 3(X+8)=X-3 | | y-29=38 | | 8w=5840 | | -16x^2-8x+64=0 | | 8.13-r=.23 | | 6(7y)=22y+40 |